Hematoma Expansion in Intracerebral Hemorrhage With Unclear Onset. (11th May 2021) - Morotti, Andrea; Boulouis, Gregoire; Charidimou, Andreas; Li, Qi; Poli, Loris; Costa, Paolo; De Giuli, Valeria; Leuci, Eleonora; Mazzacane, Federico; Busto, Giorgio; Arba, Francesco; Brancaleoni, Laura; et al.
Abstract : Objective: To investigate the prevalence, predictors, and prognostic effect of hematoma expansion (HE) in patients with intracerebral hemorrhage (ICH) with unclear symptom onset (USO). Methods: We performed a retrospective analysis of patients with primary spontaneous ICH admitted at 5 academic medical centers in the United States and Italy. HE (volume increase >6 mL or >33% from baseline to follow-up noncontrast CT [NCCT]) and mortality at 30 days were the outcomes of interest. Baseline NCCT was also analyzed for presence of hypodensities (any hypodense region within the hematoma margins). Predictors of HE and mortality were explored with multivariable logistic regression. Results: We enrolled 2, 165 participants, 1, 022 in the development cohort and 1, 143 in the replication cohort, of whom 352 (34.4%) and 407 (35.6%) had ICH with USO, respectively. When compared with participants having a clear symptom onset, patients with USO had a similar frequency of HE (25.0% vs 21.9%, p = 0.269 and 29.9% vs 31.5%, p = 0.423). Among patients with USO, HE was independently associated with mortality after adjustment for confounders (odds ratio [OR] 2.64, 95% confidence interval [CI] 1.43–4.89, p = 0.002). This finding was similar in the replication cohort (OR 3.46, 95% CI 1.86–6.44, p < 0.001). The presence of NCCT hypodensities in patients with USO was an independent predictor of HE in the development (OR 2.59, 95% CI 1.27–5.28, p = 0.009) and replication (OR 2.43, 95% CI 1.42–4.17, p = 0.001) population. Conclusion: HE is common in patients with USO and independently associated with worse outcome. These findings suggest that patients with USO may be enrolled in clinical trials of medical treatments targeting HE.